Measurement of urinary lipopolysaccharide antibodies by ELISA as a screen for urinary tract infection. Issue 1 (January 1991) - MacGowan, A P; Marshall, R J; Cowling, P; Reeves, D S
Abstract : Five hundred and twenty two clinical urine specimens submitted for routine microbiological examination were tested in parallel by conventional microscopy and culture and for lipopolysaccharide antibodies by an enzyme linked immunoabsorbent assay (ELISA) to assess the ELISA as a screen for urinary tract infection. When the ELISA alone was compared with routine methods the specificity sensitivity, and predictive value of positive and negative tests was 73.2%, 75.7%, 51.1% and 38.5%. For ELISA with microscopy the same variables were 71.1%, 82.2%, and 92.4% and 94.7%, respectively. The ELISA absorbency increased with increasing bacterial numbers, but results varied widely. Only 65.4% of urines which contained greater than or equal to 10(5) bacteria/ml were positive by ELISA; 36.8% of urines with less than 10(3) bacteria/ml were positive by ELISA; 100% of greater than or equal to 10(5) bacteria/ml cultures of Pseudomonas sp (n = 4), Staphylococcus aureus (n = 3), and Streptococcus faecalis (n = 2) were positive by ELISA but only 71.4% of Proteus sp (n = 7), 61.4% coliforms (n = 70), and 25% of coagulase negative staphylococci (n = 4). It is concluded that further development is required before the ELISA can be used for routine screening for urinary tract infection.